A preliminary discussion on the need of improving leadership ethics for youth voluntary organization development in Malaysia - Romzi Ationg; Mohd. Sohaimi Esa; Abang Mohd Razif Abang Muiz; Mohd. Azri Ibrahim; Suraya Sintang; Sirahim Abdullah (Pennwell Corporation, 2020)
This paper presents a brief discussion on the need of improving leadership ethics for youth voluntary organizations development, which referring to views and opinions expressed by scholars and researchers on youth leadership. For this reason, this paper also presents a conceptual description of several concepts pertaining to youth, leadership and youth voluntary organization in Sabah, Malaysia. Thus, this paper comprises of several subtopics, namely youth and its classification, youth voluntary organization, the leader and leadership, the leadership ethics, and the needs for improvement of leadership ethics among youth leaders. It is hoped that this preliminary discussion on the need of improving leadership ethics among the leaders of youth voluntary organization provides opportunity for national development that focuses on youth development